Modelling compensation policy for quality and delay deterioration in rail transport - Molková Tatiana; Hruban Ivo (Sveuciliste u Zagrebu, 2013)
The paper deals with the customers' claims on provided services during train delay in personal railway transport. There is comparison between the situation in the Czech Republic (Brno main station) and Austria (Wien Westbahnhof) in the paper. The development of the compensation policy cannot be based only on customer requirements. If the railway company focuses on providing compensation for delays, it must follow its economic balance. However, as the passengers' opinion survey showed, the negative impact of delays can be reduced by providing adequate information to passengers. Based on the passengers' opinion survey, it is necessary to consider the Regulation 1371/2007/ES as the minimum of the possible and on the basis of this reasoning to compile a compensation policy. The costs associated with compensation for the delay should be divided according to the causes of the delay among the individual culprits, so that railway undertakings bear the responsibility even for delays arising from reasons that are beyond the control of the railway undertaking itself.
Modelování kompenzace odklonů od kvality v železniční dopravě
Keywords: quality; railway transport; delay; compensation; modelling; kvalita, železniční doprava, zpoždění, kompenzace, modelování